Fish skin, a sustainable material used from ancient times to today’s fashion - Rahme, Lotta (FormAkademisk, 2021)
The use of fish skin is an ancient tradition in Arctic societies along rivers, streams and coasts all over the world. Fish skins were regarded as a useful material for parkas, boots, mittens and hats. Today the interest in making use of fish skin, an undeveloped by-product, is on the rise. By using different tanning techniques from cultures around the globe, fish skin has shown great promise as a material for clothing, as well as other products. There is also a desire to be able to tan these skins with environmentally friendly techniques. Today most animal skins are tanned using chromium and other cheap toxic substances, raising question around health and environmental safety. The knowledge of how to use these traditional tanning methods has been preserved by woman from cultures along the Arctic Circle stretching from the Nordic countries to Canada and Japan. In order to keep this knowledge alive for future generations, Sweden has re-introduced the possibility to receive a Master tanner´s title, increasing the incentive and status for those studying these important subjects. This is a report and narrative review of the field, and insights I have acquired over 3 decades; from student to Master Tanner.